ANALISIS PERANAN BAZNAS DALAM PENGEMBANGANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KOTA BUKITTINGGI - Ahmad Hizbul Mudzakki; Gusril Basir (Adisam Publisher, 2024)
The background for the preparation of this thesis is because the author feels that it is necessary to study the role of the BAZNAS of Bukittinggi City in supporting creative industry-based MSMEs in the city of Bukittinggi in a program to improve the people's economy. The formulation of the problem in writing this thesis is what is the role of the Bukittinggi City BAZNAS in the development of creative industry-based Micro, Small and Medium Enterprises (MSMEs) in the city of Bukittinggi. The purpose of this study is to examine the role of BAZNAS in strengthening the role of micro, small and medium enterprises (MSMEs) in the creative economy in the city of Bukittinggi. This research is a qualitative field research, namely research that shows and interprets a study that describes events in the field, or a study that seeks to describe a phenomenon that is developing.